If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + 3xy = x Combine like terms: 3xy + 3xy = 6xy 6xy = x Solving 6xy = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1x + 6xy = x + -1x Combine like terms: x + -1x = 0 -1x + 6xy = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-1 + 6y) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + 6y)' equal to zero and attempt to solve: Simplifying -1 + 6y = 0 Solving -1 + 6y = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 6y = 0 + 1 6y = 0 + 1 Combine like terms: 0 + 1 = 1 6y = 1 Add '-6y' to each side of the equation. 6y + -6y = 1 + -6y Combine like terms: 6y + -6y = 0 0 = 1 + -6y Simplifying 0 = 1 + -6y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| Y=1/4(4)^3/2 | | 5(m-2)+36=t | | 13b-4=20+9b+20 | | -8p+14=22 | | 0=-5*y*y+10xy+50x | | 0.5abc-2ac= | | -6-1=x-21 | | -4m=21 | | 2x^2+2x-260=0 | | T-35=74 | | 6/144 | | 2(v-5)-4=-5(-3v+2)-3v | | 11.2x=556 | | 11+[-3c]-4c= | | 3/x-1/3=1/4 | | 9+1.2(7n-26)-8n= | | b-1.6/4=3 | | -3+x^2=50 | | 4c/3=6c-112 | | 7y-2.2=3y | | 5/12(x-5)=3 | | 18.2x=1820 | | 2n+(-6)=2n-5 | | 1/4x3/7x4/5= | | 8x-3x+99=8x+36 | | 11c-16=-6-c+12c | | 7a/=4a-117 | | 6b+3b+14= | | 5n/4=4n-44 | | 5w^2+2w-7=0 | | 54-11x=16+8x | | x+0.75x=91 |